2009
DOI: 10.1083/jcb.200908115
|View full text |Cite
|
Sign up to set email alerts
|

Valosin-containing protein (VCP) is required for autophagy and is disrupted in VCP disease

Abstract: Accumulation of autophagosomes because of impaired autophagy during valosin-containing protein (VCP)–linked dementia is explained by the absence or reduced activity of VCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
465
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(488 citation statements)
references
References 51 publications
20
465
2
1
Order By: Relevance
“…In a control situation, ammonium chloride treatment leads to the accumulation of Lc3-II proteins due to the blockade of the lysosomal degradation of Lc3-II. Interestingly, we did not find significantly elevated Lc3-II levels in ammonium chloride treated MO- vcp -injected zebrafish embryos compared to DMSO-treated Vcp morphants, clearly demonstrating that, similar to the situation in HeLa cells and mice devoid of functional VCP [27], autophagic flux and thereby autophagic function is also impaired in Vcp-deficient zebrafish embryos. To further substantiate this finding, we assessed the impact of Vcp deficiency on the function of the autophagy system using a therefore generated novel striated muscle-specific transgenic autophagy-reporter zebrafish line Tg(unc45b:mCherry-EGFP-LC3B) and found, similar to the Lc3-II western blot analyses, impaired autophagic flux in Vcp-deficient zebrafish muscle in vivo .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In a control situation, ammonium chloride treatment leads to the accumulation of Lc3-II proteins due to the blockade of the lysosomal degradation of Lc3-II. Interestingly, we did not find significantly elevated Lc3-II levels in ammonium chloride treated MO- vcp -injected zebrafish embryos compared to DMSO-treated Vcp morphants, clearly demonstrating that, similar to the situation in HeLa cells and mice devoid of functional VCP [27], autophagic flux and thereby autophagic function is also impaired in Vcp-deficient zebrafish embryos. To further substantiate this finding, we assessed the impact of Vcp deficiency on the function of the autophagy system using a therefore generated novel striated muscle-specific transgenic autophagy-reporter zebrafish line Tg(unc45b:mCherry-EGFP-LC3B) and found, similar to the Lc3-II western blot analyses, impaired autophagic flux in Vcp-deficient zebrafish muscle in vivo .…”
Section: Discussionsupporting
confidence: 58%
“…Recently, VCP was demonstrated to be also involved in autophagic degradation of ubiquitinated substrates [26,27]. To evaluate whether autophagy-mediated protein degradation, similar to UPS-mediated degradation, is impaired by the loss of Vcp in vivo , we assessed protein levels of Sqstm1/p62 (sequestosome 1) and Lc3A/B-II, the lipidated and autophagosome-associated form of Lc3A/B or Map1lc3A/B (microtubule-associated protein 1 light chain 3) (hereafter referred to as Lc3), 2 established markers of autophagy function [28].…”
Section: Resultsmentioning
confidence: 99%
“…When viral degradation is blocked by VCP inhibition within the first few hours post infection, productive infection proceeds. A number of recent studies have shown that VCP is also required for autophagy (32,33), with the exact mechanism still subject of debate (34). Although depleting or inhibiting VCP is, thus, bound to impact this process, we consider impairment of autophagy unlikely to underlie the requirement for VCP in ADIN, since specific inhibition of the proteasome abrogates intracellular neutralization entirely [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the cellular level, both diseases are characterized by cytoplasmic protein inclusions (aggregates) positive for ubiquitin and the Tar DNA-binding Protein 43 . Analysis of IBMPFD patient-derived cell-lines and IBMPFD mouse models revealed that disease-causing point mutations in VCP affect autophagy and endolysosomal protein degradation [9,10].…”
Section: Introductionmentioning
confidence: 99%